2020
DOI: 10.1016/j.ecolecon.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding farmers' reluctance to reduce pesticide use: A choice experiment

Abstract: Despite reducing the use of pesticides being a major challenge in developed countries, dedicated agri-environmental policies have not yet proven successful in doing so. We analyze conventional farmers' willingness to reduce their use of synthetic pesticides. To do so, we conduct a discrete choice experiment that includes the risk of large production losses due to pests. Our results indicate that this risk strongly limits farmers' willingness to change their practices, regardless of the consequences on average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
87
4
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 59 publications
6
87
4
6
Order By: Relevance
“…This suggests that farmers who believe that reducing their pesticide use will benefit nature and environment (i.e., decrease environmental impacts), have a stronger intention to decrease their pesticide use. This is in line with findings of Chèze et al (2020), who found that farmers' willingness to adopt pesticide reducing practices was motivated by environmental and health gains. Furthermore, Stallman and James (2015) report that farmers who are highly concerned about the negative environmental effects of pesticides are more willing to cooperate to reduce pesticide inputs than farmers being less concerned.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that farmers who believe that reducing their pesticide use will benefit nature and environment (i.e., decrease environmental impacts), have a stronger intention to decrease their pesticide use. This is in line with findings of Chèze et al (2020), who found that farmers' willingness to adopt pesticide reducing practices was motivated by environmental and health gains. Furthermore, Stallman and James (2015) report that farmers who are highly concerned about the negative environmental effects of pesticides are more willing to cooperate to reduce pesticide inputs than farmers being less concerned.…”
Section: Discussionsupporting
confidence: 91%
“…Reported barriers include, among others: (i) the absence of non-chemical alternatives (Sporenberg, Verstand and Beerling, 2019;Tiktak et al, 2019), (ii) lack of knowledge on pesticides and alternatives, (iii) biased information from chemical companies (van den Bosch, 1989;Wilson and Tisdell, 2001), and (iv) an insufficient advisory service on judicious pesticide use (Sherman and Gent, 2014;Lamichhane et al, 2016). In addition, Chèze et al (2020) report that the risk of large production losses due to pests strongly limits farmers' willingness to reduce their pesticide use. Furthermore, economic barriers may arise because of technological lock-in due to past financial investments (Cowan and Gunby, 1996;Wilson and Tisdell, 2001) and market demands for undamaged produce (Skevas and Oude Lansink, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To our best knowledge, this scheme has not been evaluated yet. There is scope for an experimental study to analyze the impact of such an instrument on the adoption of environment-friendly practices given the numerous behavioral factors likely to influence the perceived value of such an insurance by farmers (Coble et al 2003;Chèze et al 2020). Ignoring these factors may lead to error when predicting participation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, adopting environment-friendly practices sometimes leads to greater variability in yields and costs (Knapp and Heijden 2018) not easily accepted by risk-averse farmers (Binswanger 1980;Chavas and Holt 1996;Bocquého, Jacquet and Reynaud 2014;Bougherara et al 2017;Menapace, Colson and Raffaelli 2013;Chèze, David and Martinet 2020). Farmers may choose to avoid the foreground risk of profit variability arising from risk-increasing environment-friendly practices by not engaging in them.…”
Section: Introductionmentioning
confidence: 99%
“…US farmers spent over $300 billion on pesticides in 2012 (5). Farmers are reluctant to reduce pesticide use for a complex set of reasons, including fear, crop insurance mandates, risk of lower yields and increased administrative burden (6).…”
Section: Introductionmentioning
confidence: 99%